INTERFAITH MARRIAGE IN THE CONSTITUTION AND THE ISLAMIC LAW DINAMICS IN INDONESIA - Nurcholish, Ahmad (Al-Mawarid Jurnal Hukum Islam, 2015)
Marriage between different religious believers in Indonesia is not a fabricated story. In fact, the data from various institutions which provide counseling, advocacy and facilitation for interfaith marriage, notes around 10 to 20 couples each month getting married officially or religiously. Yet, this fact is disregarded, and even covered as nothing happens. Those who do interfaith marriage are queer and even breaking religious teachings and conducting promiscuous sexual acts. This paper, then, will describe three important points about interfaith marriage in Indonesia. First, how is the constitution in Indonesia regulating this marriage? Is there any regulations clearly banning or allowing it? Second, how is the religious law, specifically Islamic law, provide foundation and legal arguments? Third, how is the practice of interfaith marriage in Indonesia? Why do some of them choose to go abroad for having their interfaith marriage? How is interfaith marriage technically held in Indonesia and possible to be acknowledged formally? Apart from those three main points above, this paper will also discuss the dynamics of interfaith family. In particular, the discussion on the living in diversity, respect and appreciation, and how children education is done, especially the religious one. Keywords : Marriage, Interfaith Marriage, Positive Law, Constitution, Islamic Law.